How do the cognitive processes matter in the event-based preschoolers’ prospective memory? - Szpakiewicz, Elżbieta; Stępień-Nycz, Małgorzata (Frontiers in Psychology, 2024)
Background: Prospective memory (PM) is the ability to remember to perform an intended action at a specific future moment. The current study examined the impact of age, task focality, and cue salience on PM in children aged 2 to 6 years, based on the multiprocess theory of PM and the executive framework of PM development. Additionally, the study explored the relationship between various cognitive abilities and their association with PM performance.Methods: A total of 224 preschool-aged children, aged 2-6, engaged in event-based PM tasks with varying cognitive demands. The tasks were either focal or nonfocal, with salient or nonsalient cues. Additionally, individual differences in cognitive abilities were measured.The results support previous indications that even very young children can successfully complete event-based PM tasks. The accuracy of PM display improved with age, especially between the ages of 3 and 4. Better performance was observed in focal PM tasks compared to nonfocal PM tasks. Additionally, preschoolers' PM performance correlated with various cognitive abilities, including fluid intelligence, retrospective memory, inhibitory control, working memory, and language ability. These correlations varied depending on the child's age and the task's nature. For both focal and nonfocal PM tasks, cognitive abilities partially mediated the relationship between age and PM performance.In summary, this study comprehensively explores the specific roles played by age and fundamental cognitive abilities in event-based PM performance among preschool-aged children.